Comparative study of hydrogen embrittlement in stable and metastable high-entropy alloys. (June 2018) - Ichii, Kenshiro; Koyama, Motomichi; Tasan, Cemal Cem; Tsuzaki, Kaneaki
Abstract: We investigated the effects of hydrogen on the mechanical response and embrittlement behavior of Fe20Mn20Ni20Cr20Co and Fe30Mn10Cr10Co (at.%) alloys precharged with 100 MPa hydrogen gas. These alloys can be classified as stable and metastable austenite-based high entropy alloys (HEAs), respectively. We carried out tensile tests at initial strain rates of 10 −4 and 10 −2  s −1 at ambient temperature. Both HEAs revealed hydrogen embrittlement associated with localized plasticity-assisted intergranular crack initiation. It is important to note that hydrogen-assisted cracking of the metastable HEA occurred via localized plasticity for both the austenite and ε-martensite phases – an unusual observation for the latter. Graphical abstract: Unlabelled Image